PENGARUH PERCEIVED SERVICE QUALITY, PERCEIVED VALUE, CUSTOMER SATISFACTION TERHADAP CUSTOMER LOYALTY PENGGUNA JASA GRABFOOD DI SOLO RAYA - Shinta Hari Fitriana; Ari Susanti (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this research is to realize and analyze the Influence of Perceived Service Quality, Perceived Value, Customer Satisfaction on Customer Loyalty of GrabFood Service Users in Solo Raya. The sample in this research was 140 persons with data assembly techniques by questionnaires. Hypothesis tough uses multiple linear regression analysis and then the data is treated with the SPSS 23 suite. The results of this research presented that perceived service quality and perceived value did not have a significant influence on customer loyalty. Customer satisfaction has a significant impact on customer loyalty. Keywords: Quality of Service, Value, Customer Satisfaction, Customer Loyalty.